Development of Multi-Criteria Decision Making Model in the Packaged Beverage Industry to Minimize Production Costs and Maximize Machine Utility using the Step Method - Puryani, Puryani; Sutrisno, Sutrisno (RSF Conference Series: Engineering and Technology, 2022)
The packaged beverage industry has grown rapidly. Now a packaged beverage industry has emerged with various brands. The emergence of many competitors, requires the packaged beverage industry to implement a strategy to survive and win the competition. One of these strategies is to make savings and maximize the use of resources. The savings made are contradictory problems with maximizing the use of resources, this is due to the use of resources, for example, the use of machines will require operational costs, even though the industry must make savings.The problem above is a multi-criteria decision making problem. Multi-criteria decision-making problems are characterized by conflicting goals on a problem to be resolved. The meaning of conflicting goals is that optimizing the value of one objective function will reduce the level of optimality of the other objective functions. One of the savings in an industry is to minimize production costs, while maximizing the use of resources, one of which can be done by maximizing machine utility. To increase the competitiveness of the packaged beverage industry, it is necessary to minimize production costs while maximizing machine utility. This can be done if the company’s management implements policies to optimally achieve the two contradictory company goals. Optimization of contradictory or conflicting company goals is a multi-criteria decision-making problem. To facilitate company management in making decisions on conflicting company goals, it is necessary to develop a multi-criteria decision-making model. In this study, a multi-criteria decision-making model will be developed to optimize two conflicting objectives, namely minimizing production costs and maximizing machine utility, with limitations in the form of company resources to achieve these goals. To optimize the multi-criteria decision-making model developed using the step method. The advantage of this method when compared to other multi-criteria decision-making techniques is the iteration in determining the value of the trade-off (simultaneous search for optimal values of two conflicting objective functions). If the determination of the value of the trade-off in an iteration does not satisfy the decision maker, then the alternative value of the trade-off can be found by doing the next iteration. Optimization of the multi-criteria decision-making model will result in minimal production costs and maximum machine utility. The multi-criteria decision-making model that was developed also resulted in a production plan that was in accordance with the number of consumer demands. In addition, the production planning carried out will also be in accordance with the capacity of the warehouse, because the model developed takes into account the capacity of the warehouse.